2015
DOI: 10.3851/imp2924
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of LiCl on replication of type II porcine reproductive and respiratory syndrome virus in vitro

Abstract: Our findings imply that the LiCl has the potential to be used as anti-PRRSV therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
(39 reference statements)
1
19
0
Order By: Relevance
“…More recently, several reports have demonstrated the antiviral effect of LiCl on DNA viruses, such as herpes simplex virus [33], pseudorabies herpesvirus [30], and porcine parvovirus [7]. Lately, the antiviral effect of LiCl on RNA viruses, such as bronchitis coronavirus [13,16], transmissible gastroenteritis virus [27], and type II porcine reproductive and respiratory syndrome virus [18], has also been demonstrated. These reports indicate that LiCl might be a potential antiviral drug for other viruses.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several reports have demonstrated the antiviral effect of LiCl on DNA viruses, such as herpes simplex virus [33], pseudorabies herpesvirus [30], and porcine parvovirus [7]. Lately, the antiviral effect of LiCl on RNA viruses, such as bronchitis coronavirus [13,16], transmissible gastroenteritis virus [27], and type II porcine reproductive and respiratory syndrome virus [18], has also been demonstrated. These reports indicate that LiCl might be a potential antiviral drug for other viruses.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Recently, some reports showed that LiCl had antiviral effects against a number of viruses, such as bronchitis coronavirus (IBV), an avian coronavirus, transmissible gastroenteritis virus (TGEV), pseudorabies herpesvirus in vitro [9][10][11] and, EV-A71, a virus which also belong to the family Picornaviridae. 12 And some new reports: porcine reproductive and respiratory syndrome virus (PRRSV), 13,14 and mammalian orthoreoviruses, 15 this suggests that LiCl has the potential to become an antiviral drug. Nevertheless, it is unclear that whether LiCl had an inhibitory effect on the FMDV.…”
mentioning
confidence: 99%
“…The relative viral mRNA level decreased by more than 30% (p < 0.001) at the concentration of 10 mM and by 50% at 20 mM (p < 0.001). The authors, however, cautioned that the effect might have been dependent on LiCl presence during the early stages of viral replication (first 9 hours) and the increase of tumor necrosis factor-α, which was greater following LiCl alone than induced by the virus 2 . In vitro studies of another porcine coronavirus causing transmissible gastroenteritis indicated that LiCl (5-25 mM) acts on both early and late stages of infection and inhibits apoptosis 3 .…”
Section: Resultsmentioning
confidence: 99%